Pregnancy and newborn outcomes in arrhythmogenic right ventricular cardiomyopathy/dysplasia. (1st May 2018) - Gandjbakhch, E.; Varlet, E.; Duthoit, G.; Fressart, V.; Charron, P.; Himbert, C.; Maupain, C.; Bordet, C.; Hidden-Lucet, F.; Nizard, J.
Abstract: Introduction: The prognosis of pregnancy in patients with Arrhythmogenic Right Ventricular Cardiomyopathy/dysplasia (ARVC/D) is poorly documented. The aim of this study is to assess the cardiac risks during pregnancy and the impact of ARVC/D on fetuses/neonates/children. Methods: We included all ARVC/D women with a history of pregnancy from the ARVC/D Pitié-Salpêtrière registry. Cardiac and obstetrical events having occurred during pregnancy/delivery/post-partum periods and neonatal data/follow-up were collected. Results: Sixty pregnancies in twenty-three patients were identified between 1968 and 2016. Only two major non-fatal cardiac events (one sustained non-documented tachycardia and one ventricular tachycardia) were recorded during pregnancy in two different mothers (3% of pregnancies, 9% of mothers). None occurred during delivery or in the postpartum period. No mother developed heart failure. Beta-blocker therapy during pregnancy ( n  = 15) was associated with lower birthweight (2730 vs 3400 g, p  = 0.004). Only two preterm deliveries occurred, unrelated to cardiac condition. Caesarean section was performed in 13% of cases. Premature sudden-death occurred in 10% ( n  = 5) of children before 25 years-old including two in the first year of life. Conclusion: ARVC/D is associated with a low rate of major cardiac events during pregnancy and vaginal delivery appears safe. The risk of sustained ventricular arrhythmia seems poorly predictable and supports the continuation of beta-blockers during pregnancy. Major cardiac events were frequent in childhood, justifying close cardiac monitoring. Highlights: ARVC/D is associated with a low rate of major cardiac events during pregnancy and vaginal delivery appears safe. No haemodynamic compromise was observed during pregnancy or post-partum period. The risk of sustained ventricular arrhythmia seems poorly predictable and supports the continuation of beta-blockers during pregnancy. We recommend a multidisciplinary care with obstetricians, cardiologists, anaesthesiologist, and paediatricians. The follow-up of children revealed frequent major cardiac events including SCD in 10%, justifying close cardiac monitoring.